Configuring Software Product Line Specific Products with SMarty and PLUS: An Experimental Study on Use Case Diagrams - Nepomuceno, Thais S.; Oliveira, Edson (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2018)
Software Product Line (SPL) represents a set of systems that share common and variable elements, to meet the specific needs of a particular market segment, providing the necessary flexibility for product customization and diversification. The adoption of SPL provides several benefits, such as, the decreasing in time for building a system and reducing its cost. One of the main SPL development activities is variability management. To manage variabilities, there are several approaches widely known in literature, such as, PLUS and SMarty. Literature has no reports of experimental evaluations comparing existing approaches. With the creation of the SMarty approach, a continuous experimental evaluation process was started in relation to other approaches with the same purpose. Thus, experimental studies have been developed in recent years to demonstrate the effectiveness of SMarty in relation to other similar approaches. Thus, in this paper, we continue the process of continuous experimentation and evolution of SMarty comparing it with the PLUS method with regard to the ability to configure SPL specifics products from use case diagrams. The results did not point to the advantages of the SMarty approach over PLUS, but point out discussion points and improvements for SMarty and the experimentation process followed.